Administracja świadcząca wobec zjawiska przemocy w rodzinie - Sierpowska, Iwona (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
Countermeasures against domestic violence belong to responsibilities of public authorities. Although tasks aimed at combating domestic violence are specified at all levels of the territorial division of the country, communities and districts are most active in this regard. The most significant administration activity involves care over victims of such violence. Help provided for them focuses on overcoming crisis situations as well as regaining their independence and self-reliance. To carry out these tasks, administration bodies exercise non-imperious forms of action, and cooperate with non-public entities. The scope of the tasks as well as mode and forms of their implementation indicate that the main role is played by the serving function of administration which centres around a human being and their needs
Keywords: administracja świadcząca; pomoc społeczna; świadczenie; przemoc